Robust β-stability and β-stabilization of impulsive switched system with time-varying delays - Mukdasai K. (2014)
In this paper, we aim to study the problems of robust β-stability and β-stabilization for uncertain impulsive switched control systems with time-varying delays. By using the descriptor model transformation, Lyapunov-Krasovskii function method and linear matrix inequality (LMI) technique, sufficient conditions for robust β-stability and β-stabilization are obtained. Numerical example is presented to illustrate the effectiveness of the theoretical results. The new stability conditions are less conservative and more general than some existing results.